Factores determinantes de la demanda de depósitos a plazo de la Caja Municipal de Ahorro y Crédito de Maynas, período enero 2018- julio 2020 - Vigo Saavedra, Janicck Mariela (2022)
This research seeks to validate which are the determining factors of the demand for term deposits of the CMAC of Maynas, during the analysis period from 2008 to 2020. For this, four candidate variables are proposed that through their use will allow the approach of a model econometric multiple linear regression that will represent the demand for time deposits as dependent on such candidates. Likewise, making use of parametric tests of individual significance such as the student's t test and the p-value test, it will be verified which variables are classified as determining factors of the demand for deposits, in addition to being determining factors, relevant for the explanation and estimation of the demand for time deposits. Given this, the results obtained by this thesis show that all the proposed candidate variables (lag in the demand for deposits, passive interest rate of the Maynas CMAC, nominal exchange rate and the Loreto consumer price index) are determinants of the demand for deposits, however, making use of the variance inflationary factor test for multicollinearity, it is possible to validate that only the deposit interest rate and the nominal exchange rate are relevant determining factors of the demand for deposits at term of the CMAC of Maynas.